Decision-making style of Chinese consumer on clothing - Radam, Alias; Ali, Mass Hareeza; Yong, Siew Leng (The Journal of Global Business Management, 2011)
The purpose of this study was to investigate the style of decision making of Chinese consumer in Malaysia towards clothing. This research is based on the Sproles and Kendall’s (1986) Consumer Style Inventory (CSI). 200 Chinese consumers in Klang Valley were selected as sample. Six reliable factors of consumer decision-making styles on clothing were identified in this study, which are price/value of money, confused by over choice, habitual/brand-loyal, novelty/fashion consciousness, brand consciousness, and impulsive/careless. The findings in this study were useful in helping marketer to reallocate their marketing strategies and provide information to marketers about the consumer’s decision-making profile of Chinese consumers in particularly in Malaysia.